1998
DOI: 10.1111/j.1540-8167.1998.tb00862.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Intraoperative Multisite Ventricular Pacing on Left Ventricular Function and Activation/Contraction Sequence in Patients with Depressed Ventricular Function

Abstract: Simultaneous right and left ventricular apical pacing results in acute improvements in global ventricular performance in patients with depressed ventricular function. Improvements may result from pacing-induced global coordination through recruitment of left and right ventricular apical and septal segments critical to effective ventricular contraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
1
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(84 citation statements)
references
References 12 publications
3
79
1
1
Order By: Relevance
“…Recent studies revealed a reverse remodeling in left ventricle with cardiac resynchronization therapy (Saxon et al 1998;Lau et al 2000;Stellbrink et al 2001;Sogaard et al 2002;Pitzalis et al 2002). However, changes in left atrial remodeling and effects on SEC have not been adequately evaluated.…”
mentioning
confidence: 99%
“…Recent studies revealed a reverse remodeling in left ventricle with cardiac resynchronization therapy (Saxon et al 1998;Lau et al 2000;Stellbrink et al 2001;Sogaard et al 2002;Pitzalis et al 2002). However, changes in left atrial remodeling and effects on SEC have not been adequately evaluated.…”
mentioning
confidence: 99%
“…Another significant reference is the DAVID Trial [9]. Several other papers appeared about dual-chamber pacing applied to congestive heart failure during the last decade of the former century; in fact and without expressly saying it, all aimed at correcting rightleft ventricular dyssynchrony, but mostly centering the criterion on the A-V delay [10][11][12][13][14][15][16][17][18][19]. Observe that the last reference comes from a multicenter clinical study, and it is over 17-years-old.…”
Section: Discussionmentioning
confidence: 99%
“…These conduction disturbances produce suboptimal ventricular filling, a reduction in ventricular dP/dt, prolonged duration of mitral regurgitation, and ventricular dyssynchrony (seen as abnormal or paradoxical septal wall motion), which may further impair the pumping ability of the heart. [61][62][63][64] In the presence of a long AV delay and/or an IVCD, LV activation is delayed, but atrial activation is not. Hence, both early passive LV filling and the atrial kick may occur simultaneously, resulting in deceased total transmitral blood flow and diminished preloading of the left ventricle.…”
Section: P Pe Er Rm Ma An Ne En Nt T Pmentioning
confidence: 99%